Is It Possible to Improve Motor Competence through a Structured Balance Bike Program in Preschool Children Aged 3 to 6 Years? - Rubén Navarro-Patón; Fabián Canosa-Pasantes; Marcos Mecías-Calvo; Víctor Arufe-Giráldez (MDPI AG, 2024)
This study aimed (1) to investigate the effect of a brief 9-week bike program on preschool motor competence levels and (2) to know the effects of the intervention program on gender. A total of 98 schoolchildren (3.86 ± 0.91 years) from La Coruña (Spain) participated. A pre-post-test quasi-experimental design was used with a control group (CG) made up of 39 students (18 boys) and an experimental group (EG) made up of 59 students (29 boys). Data were gathered using the Movement Assessment Battery for Children-2 (MABC-2). The data demonstrate that the CG and the EG differ significantly from one another before the intervention program in favour of CG in manual dexterity (MD; p < 0.001), balance (Bal; p = 0.003), total test score (TTS; p = 0.001), and total percentile score (TPS; p < 0.001), except in aiming and catching (A&C, p = 0.588). After the application of the 9-week intervention program based on the balance bike, these differences disappear (i.e., MD (p = 0.166), A&C (p = 0.372), Bal (p = 0.219), TTS (p = 0.306), and in TPS (p = 0.259)). The information gathered indicates that implementing intervention programs such as the one applied in this study could have a positive impact on improving motor competence in preschool-aged boys and girls, increasing its level.